Biological fire prevention through fungal degradation: Armillaria mellea alters combustibility of surface fuels in typical China Three-North forests - Furui Jian; Lixuan Wang; Dongming Ye; Guang Yang; Fengjun Zhao; Lin Zhang (Biomass and Bioenergy, 2026)

True triaxial mechanical behavior and damage mechanisms of water-saturated shale under blasting dynamic disturbance - Chongyang Wang; Sijiang Wei; Dongming Zhang; Fake Ren; Yisha Pan; Yun Lin; Yu Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Research on selection and deployment of monitoring equipment based on local stability analysis model of slope - Bangxin Zhang; Zongling Yan; Feng Xu; Lin Tan; Dongming Peng; Hong Dai (Arabian Journal of Geosciences, 2026)

The sustained expansion (2011−2022) and abrupt contraction (2023) of the Ross Sea polynyas - Xiaolu Ou; Lingqiao Cheng; Dongming Lin; Guoping Zhu (Journal of Marine Systems, 2026)

Spatially explicit nutritional landscapes couple with environmental variables to shape nekton distribution patterns - Na Zang; Wenjun Zheng; Bilin Liu; Shaoqin Wang; Xinjun Chen; Dongming Lin (Limnology and Oceanography, 2026)
Species distributions are traditionally explained by environmental gradients, yet the role of nutritional factors, particularly essential fatty acids (EFA), remains poorly understood. We test the hypothesis that zooplankton EFA form a nutritional landscape that couples with environmental variables to shape the biogeography of nekton. We integrated spatial data of zooplankton EFA (arachidonic acid (ARA, 20:4n‐6), eicosapentaenoic acid (EPA, 20:5n‐3), and docosahexaenoic acid (DHA, 22:6n‐3)) with environmental variables into joint species distribution models (JSDMs). We compared explanatory power across three model types: JSDM_Env (environmental variables only), JSDM_EFA (EFA variables only), and JSDM_EnvEFA (combined environmental and EFA variables). Spatial analysis revealed significant heterogeneity in EFA concentrations, with elevated levels of EPA and DHA concentrated in the northeastern region. Model results showed that both EFA and environmental variables were effective predictors of species distributions. The JSDM_EnvEFA model exhibited the greatest explanatory power (mean AUC = 0.96, mean R 2 = 0.40), with variance decomposition revealing that EFA explained more variance than environmental variables (EFA: 54%, environment: 32%). Notably, EPA contributed up to 37% of the total explained variance, surpassing the influence of sea surface temperature (14%). Incorporating EFA also changed the estimated strength of species associations, suggesting that co‐occurrence patterns may be shaped by shared nutritional dependencies. Our results demonstrate that EFA availability is as critical as environmental variables in determining nekton species distributions, which support the spatial coupling hypothesis, demonstrating that EFA landscapes couple with environmental variables to structure pelagic communities. These findings establish nutritional landscape as a critical dimension of marine biogeography, providing a novel framework for predicting community responses to global change.

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Divergent life-history traits in three geographically isolated populations of a migratory fish (Megalobrama terminalis) - Yaqiu Liu; Jianhua Li; Dongming Lin; Xinhui Li; Huifeng Li; Yuefei Li; Shuli Zhu; Yiqing Song; Jie Li (Hydrobiologia, 2026)

The Evidence for Nekton Distribution Modulated by Plankton Abundance in the High Seas Area of Northwest Pacific During Summer Season - Na Zang; Dongming Lin; Yizhen Shan; Bilin Liu; Xinjun Chen (Fisheries Oceanography, 2026)
Deterministic biotic interactions and abiotic conditions define species distributions and abundance, with plankton underpinning food webs to spatially structure predator distributions through bottom‐up processes. However, characterizing the mechanism underlying species abundance formation in an oceanic system remains challenging. We applied piecewise structural equation models to examine plankton abundance and environmental conditions in nekton assembly, combined with joint species distribution models to investigate the distribution associations between nekton and plankton in the high‐seas area of northwest Pacific. Results revealed that nekton distribution (fish and squid) showed significant associations with plankton abundance, where zooplankton correlations markedly surpassed phytoplankton associations. The fluctuations of plankton abundance directly influence nekton abundance, whereas the effects of environmental conditions were mediated indirectly through effects on plankton. These findings affirm the primacy of plankton abundance in driving nekton distribution and advance understanding of how bottom‐up trophic pathways modulate nekton distribution dynamics in pelagic ecosystems.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A study of the taxonomic status of a new tropical artificial island soil - Suping LIU; Shanquan LI; Xiaolin SUN; Faming WANG; Hongfang LU; Dongming LIU; Linhua WANG; Senhao WANG; Yongbiao LIN; Lulu ZHANG; Guoming QIN; Huaxing LI; et al. (Pedosphere, 2026)

Dominant governing mechanisms of deformation-seepage and dynamic evolution model of permeability in gas-containing coal under coupled stress-pore pressure - Chongzhi Wang; Bin Zhou; Shugang Li; Haifei Lin; Haiqing Shuang; Dongming Zhang; Shoujian Peng; Liang Cheng; Han Yang (Fuel, 2026)

Modulation of growth, gut-liver axis, and antioxidant defense by Bacillus tequilensis (GCB-3) in grass carp (Ctenopharyngodon idella) under high-carbohydrate diet: Insights into health enhancement and oxidative stress mitigation - Xin Wang; Dongming Zhang; Xinping Zhang; Xinyu Lei; Dan Jiang; Lili Lin; Wenli Zhu; Sibu Wang; Quan Huang; Yuxin Li; Yu-ke Chen; Zhixin Guo (Animal Feed Science and Technology, 2025)

Engineered biochar amended co-composting for greenhouse gas mitigation, nitrogen conservation, and eco-efficiency assessment - Yanyan Huang; Xu Yang; Jianhong Li; Hailong Wang; Hongzhu Yang; Tingting Yang; Dongming Zhang; Xianghui Zhang; Wenhui Lin; Caiwang Cheng; Paramsothy Jeyakumar; Ronghua Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Root exudates of Salix cupularis orchestrate the accumulation of soil carbon and nitrogen in the rhizosphere during the restoration of a desertified alpine meadow - Qi Li; Fei Yan; Dongming Chen; Jiqiong Zhou; Zhouwen Ma; Yanfu Bai; Xingpeng Hu; Congyu Ma; Abeer S. Aloufi; Feida Sun; Anna Gunina; Jian Zhang; et al. (Applied Soil Ecology, 2025)

Impact of enzymatic extruded brown rice flour on wheat-based dough properties and bread quality - Ling Chen; Xiaoxia Zhang; Meng Wang; Risi Wang; Suyun Lin; Yankun Shi; Xianghong Xu; Tianyu Qin; Jianhui Xiao; Dongming Li; Zicong Zeng (Food Bioscience, 2025)

Global research trends in Rhizodeposition-mediated soil carbon cycle: A bibliometric analysis - Dongming Chen; Fei Yan; Xuemei Fang; Jiqiong Zhou; Xingpeng Hu; Xiaoming Ma; Xin Zheng; Rui Yin; Feida Sun; Yanfu Bai; Zhouwen Ma; Yakov Kuzyakov; et al. (Applied Soil Ecology, 2024)

Lead-rivet strategy of growing perovskite nanocrystals for excellent toxicity inhibition and spinning application - Hanlong Wang; Shifeng Zhu; Jiaoyue Sheng; Feihong Gao; Lei Yang; Xili Hu; Francisco Fernández-Martínez; Longhui Lin; Chaoyu You; Dongming Xing (Journal of Hazardous Materials, 2024)

Deciphering the bioavailability of dissolved organic matter in thermophilic compost and vermicompost at the molecular level - Dingmei Wang; Liwen Mai; Zhen Yu; Kongtan Wang; Ze Meng; Xiongfei Wang; Qinfen Li; Jiacong Lin; Dongming Wu (Bioresource Technology, 2024)

Cyclic Impact Damage and Water Saturation Effects on Mechanical Properties and Kaiser Effect of Red Sandstone Under Uniaxial Cyclic Loading and Unloading Compression - Kui Zhao; Lin Zhang; Daoxue Yang; Jiefang Jin; Peng Zeng; Xing Wang; Shanhu Ran; Dongming Deng (Rock Mechanics and Rock Engineering, 2024)

Beneficial effects of indigenous Bacillus spp. on growth, antioxidants, immunity and disease resistance of Rhynchocypris lagowskii - Mahmoud M. Elsadek; Wenli Zhu; Sibu Wang; Xin Wang; Zhixin Guo; Lili Lin; Guiqin Wang; Qiuju Wang; Yuke Chen; Dongming Zhang (Fish & Shellfish Immunology, 2023)

Genome-wide identification and functional characterization of borneol dehydrogenases in Wurfbainia villosa - Xiaojing Lin; Linxuan Huang; Huilin Liang; Chen Hou; Xuli Ling; Yuanxia Chen; Peng Yang; Qingwen Wu; Haiying Zhao; Sirong Wu; Ruoting Zhan; Dongming Ma; et al. (Planta, 2023)

Spatial difference in feeding habits but similar foraging strategy for energy acquisition in jumbo squid - Yixuan Feng; Wei Song; Dongming Lin; André E. Punt; Xinjun Chen (Aquatic Ecology, 2023)

Gully characteristics across linear troughs in the southern Daliangshan, and its implications for debris mitigation - Kaijin Li; Hu Wang; Lin Deng; Dongming Li; Peisheng Luo (Bulletin of Engineering Geology and the Environment, 2023)

Individual diet specialization in the female jumbo squid Dosidicus gigas - Yixuan Feng; Kai Zhu; Dongming Lin; Xinjun Chen (Marine Biology, 2023)

Knowledge Map and Global Trends in Root Exudates Research from 2012 to 2021: a Bibliometric Analysis - Xin Zheng; Dongming Chen; Jiqiong Zhou; Qian Huang; Xingpeng Hu; Zhuxin Deng; Xuemei Fang; Feida Sun; Junming Zhao; Xiao Ma; Congyu Ma; Xinrui Yan; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Stable isotope evidence for a shift in diet with increasing energy demand for reproduction in squid Illex argentinus - Wei Song; Yixuan Feng; Dongming Lin; Xinjun Chen (Hydrobiologia, 2023)

Form identification of purple flying squid (Sthenoteuthis oualaniensis) based on gladius morphology - Kai Zhu; Dongming Lin; Xinjun Chen; Kaida Xu (Frontiers in Marine Science, 2022)
Stock structure information is an important part of bases for understanding the dynamics of cephalopod populations. Purpleback flying squid Sthenoteuthis oualaniensis is an abundant and highly productive species in tropical and subtropical waters of the Indo-Pacific region. However, it is characterized by a complex stock structure, and the stock discrimination is an urgent priority to understand basic biology and for stock assessment and management purposes. Here, we used gladius morphology to identify and discriminate the dwarf without a dorsal photophore and middle-sized typical forms of S. oualaniensis in the South China Sea. Results showed that both forms had double axes on the gladius and females consistently had a larger gladius than males. Multivariate analyses using the gladius morphometric characteristics indicated that individuals of dwarf form without a dorsal photophore were distinguished from those of middle-sized typical form, which was evidenced by the obvious groups and significant dissimilarity of gladii of these two forms. The discrimination based on the gladius morphometric characteristics showed a high rate of accuracy, in which a global discrimination accuracy was estimated to be 92.36% for both forms without regarding sexes and 65.82% for the discrimination to form and sex. In combination, these lines of evidence indicated that individuals of dwarf without a dorsal photophore and middle-sized typical forms of S. oualaniensis can be accurately distinguished using the gladius morphometric characteristics, and these results will warrant the application of the gladius to study the stock structure of S. oualaniensis and other squid else.

Fatty Acid Profile of Jumbo Squid (Dosidicus gigas) off the Peruvian Exclusive Economic Zone: Revealing the Variability of Feeding Strategies - Guanyu Hu; Zhenfang Zhao; Bilin Liu; Dongming Lin; Jiawei Liang; Zhou Fang; Xinjun Chen (Fishes, 2022)
Jumbo squid Dosidicus gigas play a critical role in the marine ecosystems and are an important commercial species in the East Pacific. Generally, three size groups have been distinguished on the basis of the mantle length (ML) of an adult. Here, fatty acid (FA) analyses of muscle tissues were used to explore the feeding strategies of D. gigas off the Peruvian exclusive economic zone in terms of different size groups and sexes. There was no significant difference in fatty acid composition between the small- and medium-sized groups, whereas the large-sized group differed significantly from other groups. The higher content of C20:4n6 and (C18:2n6 + C18:3n3) indicates that the large-sized group may feed more frequently in nearshore and deep waters. Furthermore, the niches of the three size groups were consistent with the results of fatty acid composition, with the large-sized group occupying the widest trophic niche, followed by the medium-sized group and then the small-sized group. In addition, there was evidence of trophic niche overlap between the small and medium groups. In terms of sexual variability of the small and medium groups, the fatty acid composition significantly differed between females and males. In terms of sexual variation of the large group, the fatty acid composition between females and males was similar, indicating that similar feeding strategies may be adopted by them. This study revealed the variability of the feeding strategies of three size groups of D. gigas off the Peruvian exclusive economic zone.

Evaluating the probiotic potential and adhesion characteristics of Bacillus spp. isolated from the intestine of Rhynchocypris lagowskii Dybowski - Yurou Zhang; Zhenchao Wu; Mengnan Yu; Dongming Zhang; Qiuju Wang; Lili Lin; Guiqin Wang; Mahmoud M. Elsadek; Qi Yao; Yuke Chen; Zhixin Guo (Aquaculture International, 2022)

Interannual Abundance Fluctuations of Two Oceanic Squids in the Pacific Ocean Can Be Evaluated Through Their Habitat Temperature Variabilities - Peng Chen; Xinjun Chen; Wei Yu; Dongming Lin (Frontiers in Marine Science, 2021)
Neon flying squid ( Ommastrephes bartramii ) and jumbo flying squid ( Dosidicus gigas ) are two commercially essential oceanic squids in the Pacific Ocean. An in-depth understanding of the mechanisms of their annual and interannual abundance fluctuations under environmental and climate variabilities can ensure ration and suitable management. Thus, the annual and interannual abundance fluctuations of the stock of the western winter-spring cohort of O. bartramii and D. gigas off Peru Exclusive Economic Zone (PEEZ) waters and their association with habitat temperature variabilities are explored in this study based on the historical Chinese Squid-jigging fishery data from 2003 to 2020. The habitat temperature variabilities were defined as the effective principal components of the SST at the squids’ two important habitats (spawning and feeding ground) through life histories according to the principal component analysis. The Hodrick—Prescott filter analysis was conducted to quantify the annual and interannual fluctuations of abundance and habitat temperature variabilities. Furthermore, the generalized additive model (GAM) was employed to investigate their associations. The results demonstrated different but not synchronous trends of abundance for O. bartramii and D. gigas . Regarding O. bartramii , the interannual abundance first decreased (2003∼2013) and then increased (after 2014). For D. gigas , the interannual abundance kept decreasing within 2003∼2020. Their annual trends have presented large fluctuations over years. The results of GAM indicated that using habitat temperature variabilities only can trace the abundance trend of O. bartramii and D. gigas at an interannual but not annual scale. Further studies verified that Pacific Decadal Oscillation (PDO) is a crucial factor affecting the interannual abundance trend of these two squids through the habitat temperature variabilities. However, this study indicates that the habitat temperature variabilities not only are related to other large-scale factors, which are not investigated currently at an interannual scale, but also, are combined with other small- or middle-scale factors at an annual scale on their impacts to the abundance fluctuations of these two squids. Therefore, in order to better explain the mechanisms of annual and interannual abundance fluctuations of O. bartramii and D. gigas under environmental and climate variabilities, the importance of combining other potential factors into consideration is highlighted.

MiR-221-3p regulates the microvascular dysfunction in diabetic retinopathy by targeting TIMP3 - Chongxian Wang; Yuling Lin; Yanqin Fu; Dongming Zhang; Yaping Xin (Pflügers Archiv - European Journal of Physiology, 2020)

Fatty acid composition and the evidence for mixed income–capital breeding in female Argentinean short-fin squid Illex argentinus - Dongming Lin; Fei Han; Sipeng Xuan; Xinjun Chen (Marine Biology, 2019)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Responses of root exudation and nutrient cycling to grazing intensities and recovery practices in an alpine meadow: An implication for pasture management - Geng Sun; Xia Zhu-Barker; Dongming Chen; Lin Liu; Nannan Zhang; Changguang Shi; Liping He; Yanbao Lei (Plant and Soil, 2017)

Ovarian development in Argentinean shortfin squid Illex argentinus: group-synchrony for corroboration of intermittent spawning strategy - Dongming Lin; Xinjun Chen; Yong Chen; Guoping Zhu; Jizhou Yan (Hydrobiologia, 2017)

Analyses of gene expression and physiological changes in Microcystis aeruginosa reveal the phytotoxicities of three environmental pollutants - Haifeng Qian; Xiangjie Pan; Jun Chen; Dongming Zhou; Zuoguo Chen; Lin Zhang; Zhengwei Fu (Ecotoxicology, 2012)